2016
DOI: 10.1002/gps.4417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild cognitive impairment and dementia in older non‐western immigrants in the Netherlands: a cross‐sectional study

Abstract: MCI and dementia were three to four times more prevalent in the majority of non-western immigrant groups when compared to the native Dutch population. These differences are important for planning and improving healthcare facilities. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 41 publications
0
67
0
3
Order By: Relevance
“…Healthwise, there is considerable variation among the different migrant groups. (Inter)-individual variation aside, older adults from Turkish and Moroccan descend are generally found to be in worse health compared to their native Dutch peers (van der Wurff et al 2004;Parlevliet et al 2016).…”
Section: Migrant Agingmentioning
confidence: 99%
“…Healthwise, there is considerable variation among the different migrant groups. (Inter)-individual variation aside, older adults from Turkish and Moroccan descend are generally found to be in worse health compared to their native Dutch peers (van der Wurff et al 2004;Parlevliet et al 2016).…”
Section: Migrant Agingmentioning
confidence: 99%
“…These findings support the cognitive reserve hypothesis, which states that individual differences in the cognitive processes underlying task performance allow some people to cope better than others with brain pathology [ 17 ]. In the Netherlands, a recent study suggests that dementia prevalence might be higher in Turkish and Moroccan immigrants than in native Dutch people [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study recruiting 2,254 participants aged 55 years or older in the Netherlands revealed that MCI was three times more frequent in most non-western migrants compared to the native Dutch population. In addition, a relevant variability of MCI prevalence across different immigrant groups was observed [18]. Such heterogeneity can be attributed to various determinants (e.g., vascular risk factors, educational level, lifestyles, physical activity, social interactions [19][20][21]) that have robustly been associated with the risk of cognitive disturbances and that were unavailable for the present analysis.…”
Section: Discussionmentioning
confidence: 91%